A comparative study between BMI and health-related physical fitness among secondary school students in M’sila - guerra, lotfi; naceur, Abdelkader; benzidane, houcine (sports creativity, 2024)
it is considered as a starting point through which the researcher This study aimed to reveal the differences between the body mass index and the health-related elements of physical fitness that constitute (cardiorespiratory fitness, muscular endurance, muscular strength, flexibility) in the research sample. The hypotheses stated that there are no differences between the body mass index and the health-related elements of physical fitness, the components of which consist of (800-meter test, sitting from a prone position with knees bent and hands on the chest, inclined prone position, bending and extending the arms, sitting tall and extending the arms forward), as the study included A sample of 17 students from the age group 14 to 16 years M'Sila